PENERAPAN METODE REGRESI LINEAR MEMPREDIKSI TINGKAT PENJUALAN SEPEDA MOTOR HONDA PADA PT. PLATINA MULIA ABADI - Palma Juanta; Saut Parsaoran Tamba; Windania Purba; Yoel Ferdinand Zai; Steven Steven; Elbert Ghozali (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
This research aims to obtain predictions of Honda motorbike sales based on Honda motorbike sales data at PT. Platina Mulia Abadi is a company engaged in transportation and automotive services, especially sales of Honda motorbikes. The linear regression method is used to predict the number of sales of Honda motorbikes. The uncertainty in the number of sales of Honda motorbikes to this company has slightly hindered the company's development, because the company cannot take a definite policy regarding the sales that occur. Therefore, this company estimates future sales of Honda motorbikes for this company, so that management can estimate future consumer demand. So that the company is able to serve and provide consumer demand. To carry out estimates, the Multiple Linear Regression method is used. The results of this research obtained an estimated sales of manual motorbikes in 2023 in January of 64,003 or 64 units of Honda motorbikes in the manual category. This means that there is an increase in the number of manual Honda motorbikes by 8 motorbikes, while the results until May 2023 are 72,123 motorbikes. Through the application of this method, the estimated sales of Honda motorbikes in the next 5 months at PT. Eternal Precious Platinum can be done easily and quickly.